Arterial Switch Operation for Late-Presenting Transposition of Great Arteries with Intact Ventricular Septum: 2 Case Reports - Cools, Evelien; Nguyen, Duy-Anh; Aggoun, Yacine; Sologashvili, Tornike (Cardiology and Cardiovascular Medicine, 2020)
The arterial switch operation (ASO) is the regular procedure to correct D-transposition of the great arteries (D-TGA) with intact ventricular septum (IVS) in the first 21 days of life. We describe 2 cases where ASO was performed in late-presenting D-TGA with IVS. In both cases, despite a short preload time of left ventricle (LV) training due to complications, ASO was performed. Correction was successful, without requiring heavy postoperative support.Patients with late-presenting D-TGA with IVS may undergo ASO, even after a short first-stage period.